Use of stirred batch reactors for the assessment of adsorption constants in porous solid catalysts with simultaneous diffusion and reaction. Theoretical analysis - Bidabehere, Claudia María (2006)
A simple, pseudo-equilibrium model was derived for a catalytic system with a first order chemical reaction and simultaneous diffusive and adsorptive processes, in order to assess the corresponding kinetics and Henry law's-type adsorption parameters. Solutions from this model were compared to exact solutions from a more detailed, general model. It was shown that under most of the experimental conditions used in stirred batch reactors and the usual model considerations, it is only possible to assess apparent adsorption parameters. Also, we observed that a stable relationship between the concentrations in the gas and solid phases is reached. The error produced in assuming that the apparent adsorption constant is the real one was calculated to be very important. The value of the apparent adsorption constant depends on various system properties and experimental conditions, such as the Thiele modulus, the amount of catalyst and the contact time. The ratio between the apparent and real adsorption constants was shown to be the transient effectiveness factor at any moment. This ratio reaches a maximum value for the pseudo-equilibrium state, that is always larger than the steady-state effectiveness factor, becoming closer as long as the system's adsorption capacity decreases. The analysis determines the operative conditions to reduce the parametric correlation. Also a criterion for the applicability of usual approximations in the assessment of kinetics and equilibrium adsorption parameters in porous solid catalysts by means of pulse injection methods is established.